2018
DOI: 10.1007/978-3-030-04537-1_12
|View full text |Cite
|
Sign up to set email alerts
|

A History of Cyber Incidents and Threats Involving Industrial Control Systems

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…According to the literature review on the major ICS attack events [4], most of the attacks have involved abnormal network behaviors. On the other hand, the literature review also has demonstrated MLtechniques yield effective classification and LSTM is suitable for time-series data.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature review on the major ICS attack events [4], most of the attacks have involved abnormal network behaviors. On the other hand, the literature review also has demonstrated MLtechniques yield effective classification and LSTM is suitable for time-series data.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…The attacks are expected to increase in number and sophistication. Therefore, critical infrastructure owners and operators must develop the ability to detect and recover from cyberattacks [4]. Therefore, protecting ICS and IIoT networks is critical for enterprises and industries.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both the C37.118 and IEC 61850 communication architectures might be vulnerable to cyber attacks [5]. Recent real-world cyber attacks on energy industrial control systems, such as the 2015 Black Energy attacks [6] and the 2017 Dragonfly 2.0 campaign [7], further highlight the importance of securing electrical power control systems.…”
Section: Introductionmentioning
confidence: 99%
“…As more critical infrastructures and industrial processes are connected via communication networks the threat of cyber-attacks on these systems increases rapidly (Hemsley and Fisher, 2018). The attacks can range from sophisticated attacks, such as the Stuxnet attack on an Iranian uranium enrichment facility (Kushner, 2013), to attacks where the attacker takes over the whole control system as in the attack on the Ukranian power grid (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%